Perbedaan Hasil Belajar Matematika Menggunakan Model Pembelajaran Make a Match dan Model Pembelajaran Pair Checks - Luthfiah Lintang; Lelya Hilda; Nur Fauziah Siregar (ARITHMETIC: Academic Journal of Math, 2021)
This study aims to determine the significant difference between the learning outcomes of mathematics using the model Make a Match learning and Pair Checks learning model on the integer material in class VII MTs IB Silaping. This type of research is a comparative study with experimental methods. The population in this study were students of class VII MTs IB Silaping totaling 92 students. The sample of this research is class VII2 b as the experimental class 1 and class VII1 a as the experimental class 2 with the same number of 16 students. The samples were determined by non-probability sampling. The data collection instrument is a test. The data analysis technique used is the normality test, homogeneity test, and to test the hypothesis with the t-test. The results of this study indicate that: (1) mathematics learning outcomes using the Make a Match learning model with an average value of 86,88; (2) mathematics learning outcomes using the Pair Checks learning model with an average value of 80,56. So it can be concluded that (3) there is a significant difference between the learning outcomes of mathematics using the Make a Match learning model and the Pair Checks learning model on the integer material in class VII MTs IB Silaping. This is in accordance with the calculation of the t-test which is obtained at the significant level is 0,05 and dk = 30 with tcount = 2,433 and ttable = 2,042 this indicates that tcount > ttable.